Existential communication concept of K. Jaspers and dialogycal personalism of M. Bakhtin: comparative analisys (Journal of Philosophy Culture and Political Science, 2023)
Abstract: This article extensively considers two main and well-known philosophical concepts of communication in the XX century through way of comparative analysis. The author explores Karl Jaspers and Mikhail Bakhtin`s directions of philosophy, which have been constructed on the base of communication and human interaction.Modern personalism, axiology and philosophical anthropology are related to the development of dialogue problem that is getting more and more relevant today at the epoch of merging and fragmentation simultaneously. Nowadays, people are tightly close to each other by technological tools, but currently separated in real life. True communication of persons, which includes loyalty and rapport are out of so-called rationalistic society`s views. Time-honored bonds between people are erasing; selfishness is increasing. That`s why existential communication concept and dialogical personalism of the greatest philosophers are still suitable for the contemporary world. These philosophical concepts were focused on searching true communication way and dialogue between people.Keywords: communication, human reason, person, consciousness, existence, human being, dialogue.